Peranan Kriya Bambu Dalam Meningkatkan Ekonomi Keluarga Pasca Pandemi Covid-19 - Siska Dwi Yulianti; Roni Fardiansyah; Barkah Yasarudin (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2022)
This research was motivated by the decline in the income of Bamboo Craftsmen in Kampung Cibiru (Kampung Egrang) Cicantayan Village, Cicantayan District, Sukabumi Regency, West Java during the pandemic so that it was affected by the economic conditions of their families. In this case, researchers want to see how the economic condition of bamboo craftsmen's families after the Covid-19 Pandemic is whether it continues to decline or increase better. Through, Bamboo Craft Art, the people of Egrang Cibiru Village, Cicantayan Village, earn income that can be used to meet their daily needs while preserving and maintaining the Bamboo ecosystem around their residences. This research uses the Phenomenological Qualitative Research Method, which emphasizes how the conditions of people's life experiences in utilizing bamboo in everyday life. The results of this study show that there is a role for bamboo crafts in improving the family economy after the Covid-19 pandemic in Kp.Ciburu, Cicantayan Village, Cicantayan District, Sukabumi Regency.